Development of the Software Engineering Education Virtual Classroom Prototype: An Experience Report - Fernandes, Filipe; Castro, Diego; Rodrigues, Claudia; Werner, Cláudia (Anais do Workshop sobre Educação em Computação (WEI), 2022)
COVID-19 pandemic forced educational institutions to reinvent themselves by using digital information and communication technologies to support the continuity of distance learning. Google Meet and Zoom were one of the tools adopted as solution. However, the learning process presented challenges, mainly related to the lack of engagement and growing demotivation of students. Immersive Learning (iL) is a research topic that has the potential to improve learning outcomes. Through immersive environments, students have access to new ways of viewing and interacting, providing more engagement in learning. Therefore, the objective of this work is to present the development of a Virtual Classroom prototype, a virtual environment to support Software Engineering Education (SEE). An initial evaluation with a specialist was carried out and it was found that the usability of the environment is satisfactory, but aspects of performance must be improved. As future work, apart from adjusting the indicated points for improvement, a user experience evaluation with 3 to 5 extended reality specialists and another evaluation with students in order to verify the influence of the Virtual Classrooms on learning outcomes will be carried out.